2014
DOI: 10.1134/s1062739114010219
|View full text |Cite
|
Sign up to set email alerts
|

Satellite monitoring of vegetation mantle response to the Sorsk copper-molybdenum mine impact

Abstract: The timely character of the digital space data utilization for regional and local day-to-day assessment of the environmental situation in the area of surface / underground mines and processing plants is proved. The natural environment situation is analyzed in terms of the Sorsk copper-molybdenum opencast mine (Republic of Khakasia, Russia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…8 Diego et al reported that the total diffused dust can be obtained quantitatively by introducing a subroutine describing particle trajectory into CFX 9 and can verify the timeliness of results and utilization of the natural environment in an open-pit mining area from satellite monitoring. 10,11 Andrade et al pointed out that the comprehensive environmental impact index was proposed after the field study in the impact on air quality by five open-pit mines, which is applicable to the impact of each air source nearby. 12 Based on the wind tunnel experiments and field tests, the emission factor of PM 10 near four typical construction sites, which is obtained from the emission factor formula 13 and exposure analysis experiment methods 14−16 of PM 10 for the soil transportation pavement, was 2−10 times higher than that of normal pavements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Diego et al reported that the total diffused dust can be obtained quantitatively by introducing a subroutine describing particle trajectory into CFX 9 and can verify the timeliness of results and utilization of the natural environment in an open-pit mining area from satellite monitoring. 10,11 Andrade et al pointed out that the comprehensive environmental impact index was proposed after the field study in the impact on air quality by five open-pit mines, which is applicable to the impact of each air source nearby. 12 Based on the wind tunnel experiments and field tests, the emission factor of PM 10 near four typical construction sites, which is obtained from the emission factor formula 13 and exposure analysis experiment methods 14−16 of PM 10 for the soil transportation pavement, was 2−10 times higher than that of normal pavements.…”
Section: Introductionmentioning
confidence: 99%
“…The dust particles with various sizes showed a similar average escape time, while the maximum escape time and escape rate decreased with the increase of particles . Diego et al reported that the total diffused dust can be obtained quantitatively by introducing a subroutine describing particle trajectory into CFX and can verify the timeliness of results and utilization of the natural environment in an open-pit mining area from satellite monitoring. , Andrade et al pointed out that the comprehensive environmental impact index was proposed after the field study in the impact on air quality by five open-pit mines, which is applicable to the impact of each air source nearby …”
Section: Introductionmentioning
confidence: 99%
“…На полученных индексных изображениях более ярко и контрастно выделяются искомые объекты по сравнению с исходным снимком. Одним из основных методических приемов было использование вегетационного индекса NDVI, который характеризируют состояние растительности [9]. NDVI это -нормализованный относительный индекс растительности -простой количественный показатель количества фотосинтетически активной биомассы.…”
Section: Introductionunclassified